1990
DOI: 10.1104/pp.92.4.1169
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Stimulates Growth of Panicum coloratum through Enhanced Photosynthesis

Abstract: A sodium-requiring C4 plant, Panicum coloratum Walt. cv Kabulabula, was grown with and without sodium. Rate of nitrogen uptake and photosynthesis were measured during the recovery from sodium deficiency. The beneficial effect of sodium on growth was apparent irrespective of nitrogen source, ammonium-or nitrate-nitrogen. The For plants raised under ammonium-N, 1 mM KNO3 was replaced by 1 mm KCI and 0.5 mm (NH4)2SO4 on d 10, and when nitrate-N, 0.5 mm (NH4)2SO4 was replaced by 1 mM KNO3, respectively, then gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The loss of Chl is usually accompanied by inactivation of photochemical reactions, especially those mediated by PSII in plants exposed to salt stress (Sharma and Hall, 1992). Enhanced activities of enzymes, such as chlorophyllase, hydroxylase, and dioxygenase, accelerate the catabolism of Chl (Matoh and Murata, 1990), whereas the relaxation of Chl and Chl proteins induced by ion toxicity prompts the dissociation of Chl (Maimaiti et al, 2014). During the early stage (8 d), Chl b content was significantly less only in our 1.0% NaCl groups compared with the control group, whereas Chl a and Car contents were affected by lower concentrations, indicating that Chl b was more stable under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of Chl is usually accompanied by inactivation of photochemical reactions, especially those mediated by PSII in plants exposed to salt stress (Sharma and Hall, 1992). Enhanced activities of enzymes, such as chlorophyllase, hydroxylase, and dioxygenase, accelerate the catabolism of Chl (Matoh and Murata, 1990), whereas the relaxation of Chl and Chl proteins induced by ion toxicity prompts the dissociation of Chl (Maimaiti et al, 2014). During the early stage (8 d), Chl b content was significantly less only in our 1.0% NaCl groups compared with the control group, whereas Chl a and Car contents were affected by lower concentrations, indicating that Chl b was more stable under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress increases chloroplast enzyme activity and acceleration of Chl decomposition (Megdiche et al, 2008), and decreases photosynthesis (Stępie n and K1obus, 2006). Furthermore, activities of phosphoenolpyruvate carboxylase and ribulose bisphosphate carboxylase are reduced (Seemann and Critchley, 1985), thereby adversely affecting carbon assimilation (Matoh and Murata, 1990). Another significant consequence of salinity stress in plants is the excessive generation of reactive oxygen species (ROS), such as O 2 • -, H 2 O 2 , •OH, and 1 O 2 (Apel and Hirt, 2004).…”
mentioning
confidence: 99%
“…This is the first time photosynthetic response to Na + addition has been measured in a major perennial crop. Previous studies identified the potential for an increase in photosynthetic capacity in C4 plants (Matoh and Murata 1990, Murata and Sekiya 1992), where Na + has been considered essential by several workers and where the stimulation has been attributed to enhanced conversion of pyruvate to phosphoenolpyruvate (Johnston et al 1988), and in part to the facilitation of Na + /pyruvate cotransport at the chloroplast envelope (Ohnishi et al 1990). In a previous study on non‐perennial C3 species, no stimulatory influence of Na + addition on photosynthesis was seen (Subbarao et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In some C4 plant species, such as members of the Panicum , Atriplex and Kochia genera, Na + has been considered an essential micronutrient by some (Brownell 1965, Brownell and Crossland 1972) and a ‘functional nutrient' by others (Subbarao et al 2003). In these species, it can stimulate photosynthesis and be involved in the Na + ‐coupling of trans‐membrane transport events (Ohta et al 1988, Matoh and Murata 1990, Ohnishi et al 1990, Murata and Sekiya 1992), although this does not appear to apply to the major crop species corn, sorghum and sugarcane (Ohnishi et al 1990, Murata and Sekiya 1992). In a variety of other, non‐C4 species, Na + , albeit not required for growth, can still have beneficial effects, especially so in the Chenopodiaceae (Lehr 1953, El‐Sheikh and Ulrich 1967, 1970, Draycott and Durrant 1976, Marschner et al 1981, Subbarao et al 2003), but also in other, commercially important, species, such as flax, ryegrass and the cereals such as oat, wheat and barley (Lehr 1953, Montasir et al 1966, Hylton et al 1967, Leigh et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Although halophytes can cope with large amounts of NaCl, essential requirement of in plants was often negated. Early studies put forward the conclusion that is required for , which was critically checked repeatedly (Ohta et al, 1987;Matoh and Murata, 1990;Brownell and Bielig, 1996) so that it now appears to be well established that at least in a certain group of (,,Na-type is required for light-dependent active into the chloroplasts of the mesophyll tissue for (Ohnishi and Kanai, 1987;Ohnishi et al, 1990;Aoki and Kanai, 1997). An early report also claimed that the CAM-plant Kalanchoe tubiflora needs for CAM but not when performing .…”
Section: In Thementioning
confidence: 99%